Correction: The burden of respiratory conditions in the emergency department of Muhimbili National Hospital in Tanzania in the first two years of the COVID-19 pandemic: A cross sectional descriptive study. - Harrieth P Ndumwa; Erick A Mboya; Davis Elias Amani; Ramadhani Mashoka; Paulina Nicholaus; Rashan Haniffa; Abi Beane; Juma Mfinanga; Bruno Sunguya; Hendry R Sawe; Tim Baker (PLOS Global Public Health)
[This corrects the article DOI: 10.1371/journal.pgph.0000781.].